The role of gut microbiota-gonadal axis in ovary activation of Asian honey bee (Apis cerana) queens - Chonghui Zhao; Yehua Peng; Wenfeng Li; Muhammad Fahad Raza; Wenbo Wang; Yi Zhang; Yanping Chen; Jun Guo; Shaokang Huang; Richou Han (npj Biofilms and Microbiomes)
Abstract The gut microbiota-gonadal axis is increasingly recognized, but its reproductive roles remain unclear. Here, we used the Asian honey bee Apis cerana queens as a model to investigate the role of the gut microbiota-gonadal axis on ovary activation. By artificially caging and releasing the mated queens for a short or long period and monitoring the morphological changes of their ovaries, we confirmed that the activation and suppression of the queen ovary could be switched quickly. We found that the ovary weight was positively correlated with the body weight. 16S rRNA sequencing showed ovarian deactivation reduced gut Lactobacillus abundance. Untargeted metabolomics identified purine metabolism as the dominant ovarian pathway, while correlation analyses implicated Lactobacillus in modulating ovarian morphology through purine signaling. This study elucidates microbiota-gonadal crosstalk governing reproduction, providing mechanistic insights with translational potential for reproductive health management.